Hybrid electrochemical supercapacitors based on aqueous electrolyte solutions - Bakhmatyuk, B.P.; Kurepa, A.S. (Физическая инженерия поверхности, 2012)
In this paper it was investigated the system of the hybrid iodine electrochemical supercapacitor, which provides the discharge capacity over 7500 F/g. Microporous carbon material obtained by high temperature steam activation of the natural raw materials was used as an anode material for electrodes preparation. Moreover, the system of hybrid alkaline electrochemical supercapacitor was investigated, and it was proved, that additional activation of the activated carbon material in the molten NaOH can increase the available for charge surface of the material. As a result, discharge capacity per weight of active material can increase up to 342 F/g and the energy density is 6.5 times greater than value of known symmetric supercapacitors.